Dry fractionation of surface abrasion for polyphenol-enriched buckwheat protein combined with hydrothermal treatment. (1st July 2019) - Chen, Xiao-Wei; Luo, Dan-Yang; Chen, Ya-Jun; Wang, Jin-Mei; Guo, Jian; Yang, Xiao-Quan
Graphical abstract: Highlights: Surface abrasion technology was firstly applied to develop buckwheat protein. Polyphenol-enriched buckwheat protein was successful produced. Hydrothermal treatment enhanced bioaccessibility of buckwheat polyphenols. Enhanced buckwheat flavor by hydrothermal treatment. Abstract: Buckwheat constitutes a good source of bioactive components. A dry fractionation of surface abrasion for polyphenol-enriched protein combined with hydrothermal treatment was evaluated as an alternative to conventional wet extraction from tartary buckwheat ( Fagopyrum esculentum Moench ). The protein contents and the total polyphenol contents of both free and bound polyphenol gradually decreased in the order from the outer to the inner fractions. Polyphenol-enriched buckwheat protein flour was successfully enrichment with a maximum polyphenol content of 55 mg/g. Moreover, starch digestibility and polyphenols bioaccessibility of the buckwheat protein were increased with hydrothermal treatment time, while protein digestibility decreased slightly. Besides, most of the aroma compounds increased during the hydrothermal treatment. The assessment results demonstrate that the sustainability dry surface abrasion process in combination with hydrothermal treatment should be encouraged in processing functional protein fractions and improving both qualities of end use products and health benefits.